Guinea : Poverty Reduction Strategy Paper-Progress Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2012)
Poverty Reduction Strategy Papers (PRSPs) are prepared by member countries in broad consultation with stakeholders and development partners, including the staffs of the World Bank and the IMF. Updated every three years with annual progress reports, they describe the country's macroeconomic, structural, and social policies in support of growth and poverty reduction, as well as associated external financing needs and major sources of financing. This country document for Guinea, dated May 2012 is being made available on the IMF website by agreement with the member country as a service to users of the IMF website.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet